New species of Parapharyngodon (Nematoda: Pharyngodonidae) parasite of Laudakia stoliczkana (Lacertilia: Agamidae) from Turpan-Hami Basin, China - Tao Wang; Xiaofei Yan; Ziqi Jiang; Jiayi Xu; Yiyang Zhao; Chong Liu; Yi Ba (International Journal for Parasitology: Parasites and Wildlife, 2025)
A new nematode species, Parapharyngodon stoliczkana sp. nov. (Nematoda: Pharyngodonidae), is described from the cecum of Laudakia stoliczkana (Agamidae) in China's Turpan-Hami Basin, marking the first documentation of intestinal helminths in this host. Specimens were analyzed via integrative taxonomy, combining morphological (light and scanning electron microscopy) and molecular approaches (18S, 28S rRNA and COI genes). Males exhibited four labial papillae, three pairs of caudal papillae, a single spicule (67.16–77.82 μm), and lateral alae. Females possessed six labial papillae, operculated eggs (150–156 × 37–39 μm), and post-bulbar ovaries. Phylogenetic analyses of concatenated sequences (18S + 28S + COI) placed P. stoliczkana sp. nov. as a sister lineage to P. echinatus + P. micipsae (BPP = 1, BS = 99), with genetic divergences exceeding interspecific thresholds (COI p-distance: 36.34–49.53 %). Infection prevalence was 100 % (8 hosts), mean intensity 360.1 ± 41.2 helminths/host. Morphologically, the species differs from congeners in caudal papillation, spicule length, and ovarian positioning. This study resolves taxonomic ambiguities in Parapharyngodon, provides diagnostic keys, and establishes foundational molecular data for future studies on reptile-parasite coevolution in arid ecosystems.